2003
DOI: 10.1128/jb.185.21.6340-6347.2003
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties and Regulated Gene Expression of the Superoxide Dismutase from the Facultatively Aerobic Hyperthermophile Pyrobaculum calidifontis

Abstract: Superoxide dismutase (SOD) was purified from a facultatively aerobic hyperthermophilic archaeon, Pyrobaculum calidifontis VA1. The purified native protein from aerobically grown cells exhibited 1,960 U of SOD activity/mg and contained 0.86 ؎ 0.04 manganese and <0.01 iron atoms per subunit. The gene encoding SOD was cloned and expressed in Escherichia coli. Although the recombinant protein was soluble, little activity was observed due to the lack of metal incorporation. Reconstitution of the enzyme by heat trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…P. aerophilum IM2 cultures derived from DSMZ strain 7523 were generously provided by Christopher House, Penn State University. Cultures of P. aerophilum were grown in media containing (per liter) 10 g NaCl, 1.3 g (NH 4 ) 2 The complete medium preparation was adjusted to pH 6.8 and sterilized by autoclaving.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. aerophilum IM2 cultures derived from DSMZ strain 7523 were generously provided by Christopher House, Penn State University. Cultures of P. aerophilum were grown in media containing (per liter) 10 g NaCl, 1.3 g (NH 4 ) 2 The complete medium preparation was adjusted to pH 6.8 and sterilized by autoclaving.…”
Section: Methodsmentioning
confidence: 99%
“…The complete genome sequence of P. aerophilum was published in 2002 (23). The genome sequences of four additional Pyrobaculum species (P. arsenaticum, P. calidifontis, P. islandicum, and Thermoproteus neutrophilus [to be reclassified as a true Pyrobaculum]) have recently been completed (T. M. Lowe et al, unpublished data), providing a valuable resource for comparing gene content to respiratory characteristics within a closely related group of crenarchaea (Table 1).A number of Pyrobaculum gene products have been characterized by heterologous expression or purification of native proteins, helping to identify genes for aerobic growth, oxidative stress, and denitrification (1,4,5,18,27,44,66). Although Pyrobaculum species are among the best-studied archaeal iron respirers, and are the only known archaeal arsenate respirers, the genes required for archaeal arsenate and iron respiration have not been identified (20,21,29,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In industry, a major requirement for commercial SODs is thermal stability, because thermal denaturation is a common cause of enzyme inactivation. It has been reported that SODs were isolated from hyperthermophiles of the genera Sulfolobus, Aquifex, Pyrophilus, Pyrobaculum, and Aeropyrum (Lim et al, 1997;Knapp et al, 1999;Amo et al, 2003). The primers for PCR used in the study Primer name Sequence (5'-3') Purpose…”
mentioning
confidence: 99%
“…18) In Escherichia coli, Fur down-regulates the sodA gene, which encodes Mn-superoxide dismutase, but up-regulates sodB, which encodes Fe-superoxide dismutase, via re- pression of the small RNA RyhB, leading to rapid degradation of the sodB transcript. 19) Several bacterial Fur deletion mutant strains are known to be sensitive to ROS.…”
Section: Estimation Of the Essential Recognition Region Formentioning
confidence: 99%